Ethnicity, Identity and Conflict as Portrayed in the Writings of V. S. Naipaul: Exploring the complexity of ethnicity, identity, and conflict in India through V. S. Naipaul's writings (Journal of Advances and Scholarly Researches in Allied Education, 2019)
India is one of the most complicated, complex yet unique agglomeration of diverse ethnic groups. Though India is a secular nation, ethnic and religious conflicts between various groups are recurrent and it’s not limited to any one place. V.S Naipaul’s India a million mutinies now is a radical insight of his journey across India in late 1980’s when Naipaul traversed various places namely Bombay, Madras, Karnataka, Tamil Nadu, Bengal, Lucknow, Punjab and Kashmir. V. S. Naipaul has established himself as a powerful member of the English Literary scene one whose memoirs reflect India in its true entirety. Out of the many interviews taken by Naipaul, a few truly encapsulates the stress and agitation prevalent in so called multicultural and multiethnic India. During the interviews he became a listener to hatred and violent clashes, between various communities where ethnicity became divisive. The paper discusses India and its heterogeneous ethnicity in the late 20th century.